Networked Digital Technologies Third International Conference, NDT 2011, Macau, China, July 11-13, 2011. Proceedings - Fong, Simon; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the proceedings of the Third International Conference on Networked Digital Technologies, held in Macau, China, in July 2011. The 41 revised papers presented were carefully reviewed and selected from 127 submissions. The papers are organized in topical sections on information security, networks, information management, multimedia, human computer interaction and simulation, e-learning and e-government, Web services/semantics, user centric information system/intelligent computing, and data mining.
Keywords: Computer science; Computer Communication Networks; Software engineering; Database management; Information storage and retrieval systems; Information systems; Artificial intelligence; Computer Science; Information Systems Applications (incl.Internet).; Artificial Intelligence (incl. Robotics).; Computer Communication Networks; Information Storage and Retrieval; Database Management; Software Engineering